Do intercultural teams need “requisite variety” to be effective? - Bartel-Radic, Anne; Lesca, Nicolas (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2011)
The aim of this paper is to analyse the impact of ‘requisite variety’ of an intercultural team on its effectiveness. Using a qualitative, longitudinal case-study method, five successive intercultural teams in one international company are analysed in order to question the effectiveness of the teams from the perspective of requisite variety. The results show that requisite variety is a necessary condition for team effectiveness. Yet, requisite variety is not easily actionable, and team processes moderate the link between requisite variety and team effectiveness. The team also needs enough time for forming, storming and norming, before requisite variety can have a positive impact on performing the task.